Nonlinear biaxial tensile stress path experiment without intermediate elastic unloading for validation of material model. (5th December 2022) - Takada, Yusuke; Kuwabara, Toshihiko
Abstract: A linear stress path (LSP) experiment was performed using uniaxial and biaxial tensile tests with a cold-rolled mild steel sheet (SPCD; nominal thickness: 0.8 mm) as the test material. In the LSP experiment, the contours of plastic work and the directions of the plastic strain rates, β, for a plastic strain range of 0.002 ≤  ε 0 p ≤ 0.234 were measured. Then, the Yld2000-2d yield function was used to identify a material model that accurately reproduces the experimental data. Stepped nonlinear stress path (NLSP) experiments were also performed; the NLSPs consisted of several linear stress paths without intermediate elastic unloading. The measured work hardening behavior and β values were compared with those calculated using the yield functions identified from the LSP experiment, namely the von Mises, Hill's quadratic, and Yld2000-2d yield functions. For the Yld200-2d yield function, both isotropic and differential hardening models were investigated. It was found that the data measured in the NLSP experiment are consistent with calculation results obtained using the Yld2000-2d yield function identified from the LSP experiment. Thus, it can be concluded that within the range of stress paths adopted in the NLSP experiment, the deformation behavior of a test sample can be accurately predicted using the material model identified from an LSP experiment.